Interpreting immune evasion: a novel assay for HLA loss detection - Pettersson, Linnéa; Westerling, Sofia; Ramezanali, Hamid; Vezzi, Francesco; Eckerud, Rikard; Hauzenberger, Dan; Hedrum, Anders; Mattsson, Jonas; Uhlin, Michael; Uzunel, Mehmet (Frontiers in Immunology, 2025)
This study presents the analytical performance of a new Next-Generation Sequencing (NGS) assay designed to detect Human Leukocyte Antigen (HLA) loss. Unlike existing methods, this assay offers increased sensitivity, broader applicability, and does not require prior knowledge of specific HLA mismatches, making it a more versatile tool for post-transplant monitoring. The main goal was to determine whether this assay can reliably identify HLA loss in post-transplant patients and provide clinically actionable information for relapse management. Furthermore, the clinical utility of the assay was assessed in patients undergoing Hematopoietic Stem Cell Transplantation (HSCT) with haploidentical or HLA-mismatched unrelated donors (MMUD). The study included both artificial and clinical samples, which were analyzed using the present assay to examine insertion-deletion (indel) markers located within and adjacent to the HLA region. The results demonstrated that the new assay exhibits excellent correlation with the One Lambda Devyser Chimerism assay in samples without HLA loss, achieving a detection limit of 0.25%. Furthermore, the study showed that the markers employed in the assay can effectively identify the occurrence and location of HLA loss. These findings could potentially influence clinical decision-making, when the donor source of retransplants or Donor Lymphocyte Infusions (DLI) need to be re-considered.